2009
DOI: 10.1093/ndtplus/sfp112
|View full text |Cite
|
Sign up to set email alerts
|

MPO-ANCA crescentic glomerulonephritis complicated by membranous nephropathy: MPO demonstrated in epimembranous deposits

Abstract: An elderly woman presented with haematuria and proteinuria accompanied by elevated serum myeloperoxidase (MPO)-specific anti-neutrophil cytoplasmic antibodies (MPO-ANCA). A renal biopsy revealed mild mesangial proliferation with fibrocellular crescent formation and a membranous glomerular lesion. Immunofluorescence microscopy using FITC-labelled rabbit anti-human MPO antibodies revealed granular MPO deposition along the glomerular capillary walls (GCW) with a staining profile similar to that of glomerular IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In fact, EDDs in the mesangium were observed in 6 of 13 cases in a case series [7] and also in another case report [6]. Although EDDs in the mesangium are frequently observed in lupus nephritis without membranous lesions, they are not generally observed in AAG.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, EDDs in the mesangium were observed in 6 of 13 cases in a case series [7] and also in another case report [6]. Although EDDs in the mesangium are frequently observed in lupus nephritis without membranous lesions, they are not generally observed in AAG.…”
Section: Discussionmentioning
confidence: 93%
“…In a case reported by Matsumoto et al, there was MPO deposition along the GCW in the first biopsy, which disappeared in the second biopsy and was accompanied by a decreased MPO-ANCA titer after treatment. They concluded that MPO and MPO-ANCA might have been responsible for the IgG immune depositions along the GCW in their patient [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MPO, for example, has been shown to co-localize with IgG and C3 along anionic glomerular capillary walls in crescentic AAV with MN [45,46] . However, any significant injury to the GBM theoretically would result in significant pan-glomerular IC which would not be typically seen [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al reported an interesting hypothesis that MPO demonstrated in epimembranous deposits (this lesion is anionic) is highly cationic. Because BPI, elastase, and lysozyme are all cationic, ANCAs for these minor antigens might be related to the formation of immune complexes [ 15 ]. Because of the lack of renal biopsy material, we were unable to demonstrate the presence of epimembranous deposits composed of ANCAs including BPI, elastase, and/or lysozyme, which might have revealed a correlation between ANCA-associated vasculitis and MGN in this case.…”
Section: Discussionmentioning
confidence: 99%